Contrast-enhanced ultrasound imaging using pulse inversion spectral deconvolution - Khairalseed, Mawia (J Acoust Soc Am, 2019)
A contrast-enhanced ultrasound (CEUS) imaging approach, termed pulse inversion spectral deconvolution (PISD), is introduced. The approach uses two Gaussian-weighted Hermite polynomials to form two inverted pulse sequences. The two inversed pulses are then used to filter ultrasound (US) backscattered data and discrimination of the linear and nonlinear signal components. A research US scanner equipped with a linear array transducer was used for data acquisition. The receive data from all channels are shaped using plane wave imaging beamforming with angular compounding (from one to nine angles). In vitro data was collected with a tissue mimicking flow phantom perfused with an US contrast agent using PISD and traditional nonlinear (NLI) US imaging as comparison. The role of imaging frequency (between 4.5 and 6.25 MHz) and mechanical index (from 0.1 to 0.3) were evaluated. Preliminary in vivo data was collected in the hindlimb of three healthy mice. Preliminary experimental findings indicate that the PISD contrast-to-tissue ratio was improved nearly ten times compared to the NLI US imaging approach. Also, the spatial resolution was improved due to the effect of deconvolution and spatial angular compounding. Overall, PISD is a promising postprocessing technique for real-time CEUS imaging.